2023
DOI: 10.1177/00207640231174376
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hikikomori and associations with suicidal ideation, suicide stigma, and help-seeking among 2,022 young adults in Hong Kong

Abstract: Background: Young adults are at elevated risks of hikikomori (severe social withdrawal) under the COVID-19 pandemic, which could lead to psychological distress and suicidal ideation. Aims: The present study aimed to examine the associations among hikikomori, suicide stigma, suicidal ideation, and help-seeking behaviors among young adults in Hong Kong. Method: This study recruited a large sample of 2,022 young adults in Hong Kong via an online survey at the end of 2021. The participants completed the Hikikomori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…Nevertheless, prior research demonstrated an increase in hikikomori in Japan in the 2010s (Cabinet Office of the Government of Japan, 2010 ; Cabinet Office of the Government of Japan, 2019 ). Additionally, more recent studies, for example, conducted during the pandemic, found higher prevalence rates (e.g., 9.1% for hikikomori among young adults in Hong Kong) (Fong & Yip, 2023 ). Based on the Arabic version of the Hikikomori Questionnaire (HQ‐25), another recent study reported a quite high prevalence rate of 44% in Oman during the pandemic (Al‐Sibani et al., 2023 ), stressing the pressing issue of hikikomori and the need for future research in this area.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, prior research demonstrated an increase in hikikomori in Japan in the 2010s (Cabinet Office of the Government of Japan, 2010 ; Cabinet Office of the Government of Japan, 2019 ). Additionally, more recent studies, for example, conducted during the pandemic, found higher prevalence rates (e.g., 9.1% for hikikomori among young adults in Hong Kong) (Fong & Yip, 2023 ). Based on the Arabic version of the Hikikomori Questionnaire (HQ‐25), another recent study reported a quite high prevalence rate of 44% in Oman during the pandemic (Al‐Sibani et al., 2023 ), stressing the pressing issue of hikikomori and the need for future research in this area.…”
Section: Introductionmentioning
confidence: 99%
“…Two recent phenomena are noteworthy: cave syndrome, which is characterized by elevated anxiety and extreme reluctance to engage in outdoor and social activities [50]. Additionally, hikikomori-a social withdrawal and self-isolating condition that has been exacerbated due to the rigorous restrictions imposed by the pandemic along with the fear of infection [51]. Amidst the global public health crisis, the multidirectional effect of comorbid mental health conditions, loneliness, and suicidal behaviors exacerbated the risk factors in multiple folds.…”
Section: Navigating the Multidirectional Association Between Comorbid...mentioning
confidence: 99%
“…Since the term "hikikomori" became famous worldwide, its existence has been reported in other countries, especially in Asia [1][2][3][4]. However, while young hikikomori have been the focus of attention, Japan is characterized by a large number of middle-aged hikikomori living with their parents.…”
Section: Introductionmentioning
confidence: 99%